Malpractice and Obstetric Practice: The Correlation of Malpractice Premiums to Rates of Vaginal and Cesarean Delivery. Issue 1 (March 2017) - Johnson, C.T.; Choubey, V.; Satin, A.J.; Werner, E.F.
Abstract : ( Am J Obstet Gynecol. 2016;545–546) Malpractice lawsuits can influence patient care, since the burden of professional liability could change the way physicians decide to manage care. Already, liability suits have caused 22% of providers to reduce their patient volume when it comes to high-risk obstetric cases, 14% to discontinue their obstetric practice altogether, and 9% to reduce all obstetric patient volume. Considering this correlation, the authors of this paper attempted to determine how the phenomenon of professional liability might impact the rate of cesarean delivery.